2020
DOI: 10.1038/s41467-020-16640-8
|View full text |Cite
|
Sign up to set email alerts
|

Insulators for 2D nanoelectronics: the gap to bridge

Abstract: Nanoelectronic devices based on 2D materials are far from delivering their full theoretical performance potential due to the lack of scalable insulators. Amorphous oxides that work well in silicon technology have ill-defined interfaces with 2D materials and numerous defects, while 2D hexagonal boron nitride does not meet required dielectric specifications. The list of suitable alternative insulators is currently very limited. Thus, a radically different mindset with respect to suitable insulators for 2D techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
314
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 345 publications
(320 citation statements)
references
References 161 publications
(305 reference statements)
5
314
0
1
Order By: Relevance
“…Nevertheless, other dielectric alternatives based on 2D materials are being considered due to the outstanding features of the electron devices that employ them [7][8][9][10]. Intense research efforts are being conducted to describe yield, variability, reliability and stability in the field of 2D materials based solid-state nano/micro-electronic devices [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, other dielectric alternatives based on 2D materials are being considered due to the outstanding features of the electron devices that employ them [7][8][9][10]. Intense research efforts are being conducted to describe yield, variability, reliability and stability in the field of 2D materials based solid-state nano/micro-electronic devices [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, other dielectric alternatives based on 2D materials are being considered due to the outstanding features of the electron devices that employ them [7][8][9][10]. Intense research efforts are being conducted to describe yield, variability, reliability and stability in the field of 2D materials based solid-state nano/micro-electronic devices [9,10]. 2D dielectric memristor technology can lead to solutions to some of the issues that show up in memristors industrial applications linked to non-volatile memories [2,9], entropy sources for cryptographic hardware (random number generation and implementation of physical unclonable functions [2,9,11]) and, most important, neuromorphic computing [2,8,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High‐ k native dielectrics are a plus. Unfortunately, major 2D semiconductors, such as MoS 2 , WSe 2 , [ 29 ] HfSe 2 , ZrSe 2 , [ 30 ] and HfS 2 , [ 31 ] have not yet given rise to workable devices based on native high‐ k stacks by thermal oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of these native oxides as gate insulators in 2D devices has not been demonstrated so far. [ 35 ] For Hf‐ and Zr‐based TMDs, none of the currently reported TMD:oxide interfaces for 2D devices are truly native, still formed by either transfer, deposition techniques or laser writing. [ 36–38 ] Recently, Li et al [ 39 ] reported Bi 2 O 2 Se‐based MOSFETs with native Bi 2 O 5 Se as the gate dielectric which was made from Bi 2 O 2 Se by thermal oxidation, just as in traditional Si MOSFETs.…”
mentioning
confidence: 99%